Determinants of International Migration: A Panel Data Evidence from Indonesia - Salbilla Azra; Khairul Amri; Cut Dian Fitri (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This research is original in integrating education, unemployment, minimum wages, and poverty into a panel-data framework to analyze international labor migration across Indonesian provinces. Research Objectives: This study aims to investigate the impact of average educational attainment, the open unemployment rate, provincial minimum wage, and poverty rate on international migration of Indonesian workers. Research Methods: This study uses panel data from 32 provinces in Indonesia for the period 2010 to 2025 and applies a panel regression approach with a Fixed Effects Model. Empirical Results: The findings indicate significant influences from both dependent and independent variables. Average years of education, open unemployment rate, provincial minimum wage, and poverty are shown to have a negative and significant influence on the international migration patterns of Indonesian migrant workers. Implications: Policymakers should focus on affordable migration financing schemes to address poverty constraints, vocational training relevant to the international labor market, and strengthening the migration ecosystem in areas with high unemployment rates. JEL Classification: F22, I25, E24, J30, I32